ADVANTAGES AND DISADVANTAGES OF E-LEARNING IN COMPARISON TO TRADITIONAL FORMS OF LEARNING - MIRJANA RADOVIĆ-MARKOVIĆ (Annals of the University of Petrosani: Economics)
Internet education is soon to become the dominant form of education inthe world. A lot of effort is being devoted into furthering the work methods and communicationamong students and professors, aimed at bettering the quality of this kind of studying.Moreover, further development of virtual education in the future will depend on the advance ofcontemporary technologies and the Internet. Having this in mind, the author of this paper hastried to explore to what extent the previous results have been accomplished, as well as toclassify the different modalities of this kind of learning and to ascertain their advantages anddisadvantages. A special emphasis has been put on the great utility value for all developedeconomies, which have made great progress in the development rate and in the spreading ofvirtual faculties’ network. At the end of this research paper, recommendations are given, andfurther trends of Internet education are established, juxtaposed to the classic forms of studying,based on the latest research results in this field. The author especially emphasizes the fact thatfaculties with “classrooms without walls” will not fully replace traditional faculties. The valueof this paper lies particularly in the fact that it builds not only on the contemporary researchfindings, but also on the author’s personal experience as a professor engaged in this form ofstudent education.